The Development of Social Capital and Financing of Entrepreneurial Firms: From Financial Bootstrapping to Bank Funding. (21st October 2011) - Jonsson, Sara; Lindbergh, Jessica
<x xml:space="preserve">Abstract</x> This paper uses a three‐dimensional perspective on social capital to investigate how entrepreneurs develop their social capital when relying on bootstrapping strategies becomes insufficient and financing needs to be acquired from external debt and equity financiers. Findings from six case studies of entrepreneurs in the fashion industry show that to acquire funding, due to perceived deficiency in the existing network, entrepreneurs develop the structural dimension by adding relationships based on function. However, when seeking financial information that is perceived as sufficient in the existing network, they do so by developing cognitive and relational dimensions to preexisting network ties.